Contrastive Analysis of Persuasive Text Translation: An exploratory Study of Vietnamese and Chinese Students in Thailand EFL Context - Srithongkham, Kullanat (International Journal of Multidisciplinary in Management and Tourism, 2020)
The purpose of this study was to study the translation ability in rend the persuasive letters from Thai to English by Vietnamese and Chinese students learning English as a foreign language in Thailand contexts in order to analyze the differences in interpreting the source language in English and grammatical errors and discursive texts. 60 participants who have passed the course of Thai usage, 30 Vietnamese and 30 Chinese students, were selected to translate the persuasive text from Thai to English under the topic of “Let’s have exercises with family”, designed by the researchers and proved by the experts. The results showed that six common errors produced by Vietnamese and Chinese students were found in their Thai to English translation. Those errors were listed in descending order as follows: Categories of errors of wrong selection of words from source language for target language (VTN=29.34%: CHN=24.48%); noun (singular and plural) (VTN=22.82%: CHN=26.53%), subject-verb agreement (VTN=18.47%: CHN=12.24%), prepositions (VTN=17.39%: CHN=22.44%), determiners (VTN=6.52%: CHN=8.16%), and pronouns (VTN=5.43%: CHN=6.12) respectively. In addition, the results in the use of hedges and boosters found in VTN and CHN translation from Thai to English showed a very similar outcome. That was, the boosters were likely to be more dominant in both corpora. The results indicated that the students were more careful in translating the persuasive texts. Additionally, variations in the use of boosters existed in the translation of both VTN and CHN students. In the same fashion as in the hedges, it was clear that the boosters were more highly used in the two corpora especially the modal verb “should” (VTN= 16.22 per/1000 words: CHN=23.58 per/1000 words). However, the use of boosters is used higher in translation of the persuasive text from Thai to English of CHN students.